2022
DOI: 10.1371/journal.pone.0275313
|View full text |Cite
|
Sign up to set email alerts
|

Not the same CURE: Student experiences in course-based undergraduate research experiences vary by graduate teaching assistant

Abstract: To expose all undergraduate science students to the benefits of participating in research, many universities are integrating course-based undergraduate research experiences (CUREs) into their introductory biology laboratory curriculum. At large institutions, the bulk of introductory labs are instructed by graduate teaching assistants (GTAs). Graduate students, who are often teachers and researchers in training, may vary in their capacity to effectively teach undergraduates via the CURE model. To explore variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We reported that some GTAs may prioritize providing research support over emotional support to students, while others may focus solely on “content delivery”, neglecting mentorship roles in the CURE (Goodwin, Cary, & Shortlidge, 2021). In a second unit of this study, we explored course‐wide patterns between students' experiences and their GTA, demonstrating that GTAs influence student perceptions of the classroom environment, the CURE elements they engage in, and the purpose of the CURE (Goodwin et al, 2022). This current study offers an exploration of how GTAs with the same professional development experiences, and in the same instructional context, still provide different levels of mentorship and support, resulting in varying perceptions and experiences by students in the “same” CURE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reported that some GTAs may prioritize providing research support over emotional support to students, while others may focus solely on “content delivery”, neglecting mentorship roles in the CURE (Goodwin, Cary, & Shortlidge, 2021). In a second unit of this study, we explored course‐wide patterns between students' experiences and their GTA, demonstrating that GTAs influence student perceptions of the classroom environment, the CURE elements they engage in, and the purpose of the CURE (Goodwin et al, 2022). This current study offers an exploration of how GTAs with the same professional development experiences, and in the same instructional context, still provide different levels of mentorship and support, resulting in varying perceptions and experiences by students in the “same” CURE.…”
Section: Discussionmentioning
confidence: 99%
“…In SEA‐PHAGES, students experience each of the five CURE elements in that: (1) they engage in multiple Scientific Practices , including learning different scientific techniques (e.g., micropipetting, gel electrophoresis) and skills, such as data analysis and science communication (e.g., writing scientific reports); (2) they Collaborate with other students and instructors throughout the duration of the course; (3) they have opportunities to Iterate several of the experimental steps in order to successfully isolate and characterize their bacteriophages; (4) any bacteriophage they successfully isolate is likely to be Novel and previously undescribed by other scientists, due to the great diversity of bacteriophages; and (5) bacteriophage information is archived in an online database and has the potential to be useful for other scientists ( Broader Relevance ). However, the Broader Relevance of this implementation of the SEA‐PHAGES CURE is limited, as the bacterial host that students work with does not have a known relevance within the scientific community (Goodwin et al, 2022). Furthermore, students in this course are unable to conduct genomic analyses that could feasibly increase the value of a contribution to the online database (Goodwin et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a growing body of research has revealed that research experiences can vary in ways that have the potential to disrupt students’ science identity (Camacho et al, 2021; Goodwin et al, 2022; Limeri et al, 2019; Remich et al, 2016; Rodriguez et al, 2022; Thiry et al, 2012; Tuma et al, 2021). For instance, students vary in the extent to which they are epistemically involved in, or intellectually responsible for, their research (Burgin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%